THE URGENCY OF RATIFYING THE 1990 INTERNATIONAL CONVENTION ON THE PROTECTION OF THE RIGHTS OF ALL MIGRANT WORKERS AND MEMBERS OF THEIR FAMILIES - Adha, Lalu Hadi (Jurnal IUS, 2013)
The International convention on the protection of the rights of all migrant workers and members of their families explicitly regulate the rights described in the Human Rights International Standards. Several main points of the Convention of the Rights of Migrant Workers are that these conventions contribute a normative-comperhensive frame to execute national and international migration policy based on Law provisions. Those conventions provide a right-basic approach frame but not merely a human rights agreement. The conventions built a parameter for national policy and regulations and engage an agenda to consultation and cooperation among countries on the most relevant issues such as information exchange, elimination of the unregulated migration, migrant smuggling and human trafficking. The convention covered the whole migration process of migrant workers and their family members such as preparation, departure and transit, their living in the working destination country, homecoming and reintegration at their home country or domicile country. Therefore through a normative legal study with conceptual and analysis approach, this study will further find out the urgency and motivation for the state to ratify this convention.Keywords: Urgency, Ratification, Migrant Workers.